Long-term follow-up after laparoscopic versus open distal gastrectomy for advanced gastric cancer - Zhang, Ying (Int J Clin Exp Med, 2015)
This study aimed to compare the long-term outcomes of laparoscopic and open distal gastrectomy for advanced gastric cancer. Between January 2007 and December 2014, patients with advanced gastric cancer underwent distal gastrectomy by laparoscopic or open approach were identified. Patients in both groups were selected after being matched by age, gender, American Society of Anesthesiologists (ASA) class and clinical TNM stage using propensity score method, to create two comparable groups: laparoscopy and open groups, and prognosis were compared between these two groups. After the patients were matched, 86 patients in each group were selected for analysis. There were no significant differences in the clinicopathological features between the two groups. There were significant differences between the laparoscopy and open groups in terms of blood loss, duration of surgery, and hospital stay. The 5-year overall survival rate was 59% in laparoscopy group, and 56% in open group (P=0.523). The 5-year disease-free survival rate was 52% and 46%, respectively (P=0.362). According to the univariate and multivariate analysis, this type of surgical approach was not a prognostic factor for long-term outcomes. The current results indicated that laparoscopic distal gastrectomy is associated with similar overall survival and disease-free survival for advanced gastric cancer.